2020
DOI: 10.1080/20002297.2020.1848135
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal tissues are targets for Sars-Cov-2: a post-mortem study

Abstract: Background: The ability of coronavirus SARS-CoV-2 to spread is one of the determinants of the COVID-19 pandemic status. Until June 2020, global COVID-19 cases surpassed 10 million. Asymptomatic patients, with no respiratory impairment, are believed to be responsible for more than 80% of the transmission. Other viruses have been consistently detected in periodontal tissues. Objective: The aim of this study was to investigate the presence of SARS-CoV-2 in periodontal tissue. Methods: We conducted video-endoscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 30 publications
1
89
0
12
Order By: Relevance
“…Concluded that the oral cavity is an important site for SARS-CoV-2 and saliva as a potential route of COVID-19 transmission from oral droplets containing infectious virus and infected cells. In another study by Matuck et al (2020) demonstrated the presence of SARS-CoV-2 in periodontal tissue in severely ill patients (26). The authors highlight that periodontal tissue can be a target for SARS-CoV-2, and contribute to the presence of the virus in saliva.…”
Section: Discussionmentioning
confidence: 93%
“…Concluded that the oral cavity is an important site for SARS-CoV-2 and saliva as a potential route of COVID-19 transmission from oral droplets containing infectious virus and infected cells. In another study by Matuck et al (2020) demonstrated the presence of SARS-CoV-2 in periodontal tissue in severely ill patients (26). The authors highlight that periodontal tissue can be a target for SARS-CoV-2, and contribute to the presence of the virus in saliva.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of SARS‐CoV‐2 in saliva may be related to viral proliferation and RNA secretion in any cells and tissues involved in production of salivary components, such as periodontal tissue, salivary glands, and cells of the upper respiratory tract [5]. For instance, we have previously demonstrated the presence of SARS‐CoV‐2 RNA in periodontal tissue [6]. Determining how each tissue contributes as a reservoir for SARS‐CoV‐2 may be a path towards better understanding of the SARS‐CoV‐2 profile in saliva and for developing strategies for improving diagnosis, as well as for mitigating contamination through salivary droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study focused on identifying the presence of SARS-CoV-2 in oral tissues by means of PCR. The study design most used was “in silico”, followed by “in vivo” and finally “in vitro” [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Most of the articles showed a combination of two or more of the aforementioned study designs.…”
Section: Resultsmentioning
confidence: 99%